THE EFFECT OF UTILITARIAN VALUE AND HEDONIC VALUE ON LOYALTY THROUGH SATISFACTION IN SHOPEE'S E-COMMERCE (CASE STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS, UNIVERSITY OF SARJANAWIYATA TAMANSISWA) - Wayan Deni Ardane; Ida Bagus Nyoman Udayana; Bernadetta Diansepti Maharani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the effect of utilitarian value on satisfaction, the effect of hedonic value on satisfaction, the effect of satisfaction on loyalty, the effect of utilitarian value on loyalty, the effect of hedonic value on loyalty. The sample in this study were 100 active students of the faculty of economics, University of Sarjanawiyata Tamansiswa Yogyakarta who used the e-commerce shopee. The data collection method uses a questionnaire method via google form and is distributed using a purposive sampling technique. This research used data quality test, classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis and hypothesis testing. The data analysis in this study was carried out using the assistance of the SPSS program version 22. The results of this study indicate that utilitarian value has a positive and significant effect on satisfaction, hedonic value has a positive and significant effect on satisfaction, Satisfaction has a positive and significant effect on loyalty, utilitarian value has a positive and significant effect on loyalty. , and hedonic value has a negative and insignificant effect on loyalty.